Demand for bio-based fertilizers from dairy manure in Washington State: a small-scale discrete choice experiment. Issue 2 (6th April 2021) - Hills, Karen; Yorgey, Georgine; Cook, Joseph
Abstract: The use of bio-based fertilizers derived from dairy manure can provide a valuable source of fertility, improve soil health and provide an outlet for manure from dairy operations. We conducted a small-scale discrete choice survey of crop farmers and crop consultants in Washington State to determine the attributes that were important to them in the potential use of a bio-based fertilizer product derived from dairy manure. Of the attributes examined, distribution channel was not statistically significant. Respondents preferred air-dried or pelletized forms to wet forms, though there was no statistically significant difference between air-dried and pelletized forms. As expected, uptake increased as price decreased. Our results imply that respondents would be willing to pay 23 and 39% more for an air-dried or pelletized product, respectively, than for a 'semi-wet' product. Our results indicate that there are other important attributes beyond the ones in the survey that led respondents to stay with their current fertilizer regime. Qualitative responses in the survey pointed to the need for field trial results and data on nitrogen release from the bio-based fertilizer. Greater understanding of willingness-to-pay and attributes important to potential end users is important for the development of markets for bio-based fertilizers.